PENGARUH KONSENTRASI ASAM SITRAT TERHADAP KARAKTERISTIK EKSTRAK PIGMEN LIMBAH SELAPUT LENDIR BIJI TERUNG BELANDA (Cyphomandra beatacea S.) DAN AKTIVITAS ANTIOKSIDANNYA - Surianti, Nengah Sri; Agung, I Gusti Ngurah; Puspawati, GAK Diah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 1 No 1 (2012): Jurnal ITEPA, 2012)
This research aimed to determine the influence of citric acid concentration on characteristic of the pigment extract of seed jelly tamarillo waste and to determine the exact concentration of citric acid to produce the best characteristic of pigment extracts of seed jelly tamarillo waste. This research used a randomized block design with treatments concentration of citric acid concentration on five levels, such as: 2%, 4%, 6%, 8%, and 10%. The treatment was repeated 3 times in order to get 15 units experimntal. Vareabel observed were the yield, moisture content, anthocyanin total, phenol total and antioxidant activity. The results showed that the treatment is very significant on yield, total anthocyanin, and total phenols, dan significantly on water content. The best results were obtained from the treatment of citric acid concentration of 10% with characteristic yield of 42.29%, water content of 13.23%bk, anthocyanin total of 82.38 mg/100g, and phenols total of 33976.20 mg/100g. The best results pigment extract had antioxidant activity at IC50 on concentrations of 75.15 ppm.
Keywords: tamarillo, the concentration of citric acid, antioxidant activity